2015
DOI: 10.1002/pro.2734
|View full text |Cite
|
Sign up to set email alerts
|

Structure–function correlations in tyrosinases

Abstract: Tyrosinases are metalloenzymes belonging to the type-3 copper protein family which contain two copper ions in the active site. They are found in various prokaryotes as well as in plants, fungi, arthropods, and mammals and are responsible for pigmentation, wound healing, radiation protection, and primary immune response. Tyrosinases perform two sequential enzymatic reactions: hydroxylation of monophenols and oxidation of diphenols to form quinones which polymerize spontaneously to melanin. Two other members of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
131
0
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(148 citation statements)
references
References 58 publications
5
131
0
12
Order By: Relevance
“…Dioxygen is reversibly bound as peroxide in aside-on bridging coordination. [4,15,17,18] Recently,t he Fishman group presented crystal structures of the tyrosinase from Bacillus megaterium (TyrBm)with and without bound mono-or diphenolic substrates such as tyrosine, p-tyrosol, and l-DOPA. COs,i nc ontrast, can only perform the latter reaction (diphenolase activity).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dioxygen is reversibly bound as peroxide in aside-on bridging coordination. [4,15,17,18] Recently,t he Fishman group presented crystal structures of the tyrosinase from Bacillus megaterium (TyrBm)with and without bound mono-or diphenolic substrates such as tyrosine, p-tyrosol, and l-DOPA. COs,i nc ontrast, can only perform the latter reaction (diphenolase activity).…”
mentioning
confidence: 99%
“…[15,16] Besides the natural substrate tyrosine TYs also hydroxylate other monophenols in ortho-position to diphenols, followed by oxidation to ortho-quinones (monophenolase activity). [17,18] They suggested that ah ighly conserved glutamate and an asparagine bind and activate aw ater molecule towards deprotonation of monophenols,w hich is required for tyrosinase activity.H ere we provide the first direct experimental proof of this hypothesis. [15] Although being of significant biological, medical, and economic importance,t he molecular basis of the functional discrimination between tyrosinase and catechol oxidase is still unclear.…”
mentioning
confidence: 99%
“…Tyrosinase (EC 1.14.18.1), a multifunctional copper‐containing oxidase, is the key rate‐limiting enzyme in melanin synthesis, which catalyzes both the monophenolase reaction and diphenolase reaction (Kanteev, Goldfeder, & Fishman, ). Tyrosinase inhibitor can cure skin pigmentation or whiten skin (Kim et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…15,19 Di-Mn(II/III) catalases catalyze the disproportionation of hydrogen peroxide. 20 Cytochrome c oxidase (C c O) catalyzes the four-electron reduction of O 2 2123 while water is oxidized to O 2 at the Mn 4 CaO 5 oxygen evolving complex (OEC) of photosystem II.…”
Section: Introductionmentioning
confidence: 99%